Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1111/jan.14496
|View full text |Cite
|
Sign up to set email alerts
|

Private life telepressure and workplace cognitive failure among hospital nurses: The moderating role of mobile phone presence

Abstract: Aim To examine whether the presence of a mobile phone has a moderating role in the relationship between nurses’ private life telepressure and workplace cognitive failure. Design Cross‐sectional quantitative study using self‐report questionnaires. Methods Data were collected between December 2019 – January 2020. In total, 849 Registered Nurses from three Belgian hospitals completed the online survey. Data were analysed with hierarchical regression analyses and simple slope tests. Results Overall, the positive r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In this study, it is not clear whether the facilitative effect of the presence of cell phones on creativity is stronger than the disruptive effect produced by distraction. Although multiple researchers have observed negative effects of cell phone presence [28][29][30][31]59 , many others have concluded that it is di cult to replicate the effects of a cell phone's presence and that the effects can even be described as weak [60][61][62][63] . It is likely that other potential factors (e.g., task meaningfulness to participants and individual differences in emotion-related impulsivity) can moderate or limit the negative effects such that they are not evident in a wide range of situations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, it is not clear whether the facilitative effect of the presence of cell phones on creativity is stronger than the disruptive effect produced by distraction. Although multiple researchers have observed negative effects of cell phone presence [28][29][30][31]59 , many others have concluded that it is di cult to replicate the effects of a cell phone's presence and that the effects can even be described as weak [60][61][62][63] . It is likely that other potential factors (e.g., task meaningfulness to participants and individual differences in emotion-related impulsivity) can moderate or limit the negative effects such that they are not evident in a wide range of situations.…”
Section: Discussionmentioning
confidence: 99%
“…In the workplace, cell phones may trigger nonfocused attentional states, which in turn can foster creativity. In one recent study, the presence of cell phones caused cognitive failures 29 , and in other studies, the presence of a cell phone induced poor performance on cognitive tasks by reducing attentional resources available for the task 30,31 . Such effects can be attributed to attentional capture by external stimuli 30 , unconscious task-irrelevant thoughts 32,33 , and/or being in the state of permanent readiness to respond to one's smartphone 34 .…”
Section: Introductionmentioning
confidence: 88%
“…WPT disrupts the work-life balance as employees exceed their limits in favor of work (Barber, Conlin & Santuzzi, 2019). These workplace expectations may cause distractions, interruptions to daily life flow, work exhaustion, and sleep disorders (Querstret & Cropley, 2012;Cambier, Van Laethem & Vlerick, 2020;Page, Nastasi & Voyles, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Telepressure is a unique response to interpersonal social demands and encompasses the preoccupation and urge to quickly respond to message-based communication (Barber & Santuzzi, 2015 ). Despite its origin in occupational health psychology, telepressure has rapidly transformed into a more general responsiveness-related concept that can be experienced at any time throughout the day (Barber & Santuzzi, 2017 ), including boundary-crossing contexts such as workplace telepressure during leisure time (e.g., feeling the need to reply towards business emails in the bedroom; Cambier et al, 2019 ; Lutz et al, 2020 ; Van Laethem et al, 2018 ) and private life telepressure at work (e.g., feeling the need to reply towards chat messages of family and friends while having a conference call; Cambier et al, 2020 ; Lutz et al, 2020 ). Unfortunately, the pursuit of staying connected seems detrimental to well-being as employees who experience telepressure towards business communication struggle to psychologically detach from work during their leisure time (Barber et al, 2019 ; Cambier et al, 2019 ; Hu et al, 2019 ; Pfaffinger et al, 2020 ; Santuzzi & Barber, 2018 ).…”
Section: Telepressure and Affective Ruminationmentioning
confidence: 99%